Benefits of Traditional Postnatal Care (TPC) in Restoring Wellbeing of Postnatal Mothers in Kota Kinabalu, Sabah - Patricia, Sator; Nicholas Pang, Tze Ping; Rekaya, Vincent Balang; Rosalia, Saimon (Faculty of Medicine & Health Sciences, Universiti Malaysia Sabah, 2024)
TPC is an alternative method for the mother after giving birth, suitable to be studied to allow nurses to understand better the process and the effect on the mother’s health after giving birth. This study aims to identify the beneficial effects of TPC on postnatal mothers in this study setting. The researcher used a cross-sectional study approach using a modified questionnaire. This study was conducted from November 2021 to February 2022 in selected government health centres in Kota Kinabalu, Sabah. There were 178 postnatal mothers with inclusion criteria of Malaysian citizenship who delivered full-term babies and, through spontaneous vaginal delivery, participated in this study. This data is obtained within 7-10 days post-delivery. 69 of 178 participants reported practising TPC. 34 (49.3%) are aged 22-30 years old, 60 (87%) are Muslim, 23 (33.3%) are from Bajau ethnicity, 54 (79.6%) housewife, 41 (59.4%) with secondary school, 57 (82.6%) gravida 1-4, 59 (85.6%) parity 1-4, 35 (50.8%) with household income per month ranged from RM1001-RM2000 and 42 (60.9%) as a full-time employed. Some participants practised more than one type of TPC. The types of TPC practising form most to least; traditional body massage (47 practisings), body steaming (29), body wrapping (28), jamu consumption (25), body heat therapy (13), lihing consumption (6) and reflexology (2). The beneficial effects of TPC stated restoring body vitality (51 responses), getting rid of body wind (46), medical effects (19), easy to get/ practice previously (17), cheap (12), comfortable/ privacy (12), energy recovery (12), more confidence (2), good for mental and physical (2) and enhanced breast milk production (2). The most practised type of TPC is traditional body massage, and the benefit of TPC, as reported, mainly is restoring the body's vitality. TPC is vital for nurses to know, not only in modern medicine and other nursing care but also in mother’s practices and beliefs after giving birth. How it was done, who does it, the frequency and most importantly, the benefit of TPC on postnatal mother’s health and well-being. This study recommends exploring TPC practice among postnatal mothers, particularly their experiences with TPC, in future research.